2021
DOI: 10.3390/microorganisms9030618
|View full text |Cite
|
Sign up to set email alerts
|

Recognizing the Benefits of Pre-/Probiotics in Metabolic Syndrome and Type 2 Diabetes Mellitus Considering the Influence of Akkermansia muciniphila as a Key Gut Bacterium

Abstract: Metabolic syndrome (MetS) and type 2 diabetes mellitus (T2DM) are diseases that can be influenced by the structure of gut microbiota, whose improvement is often neglected in metabolic pathology. This review highlights the following main aspects: the relationship between probiotics/gut microbes with the pathogenesis of MetS, the particular positive roles of Akkermansia muciniphila supplementation in the onset of MetS, and the interaction between dietary polyphenols (prebiotics) with gut microbiota. Therefore, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
78
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 129 publications
(80 citation statements)
references
References 226 publications
(203 reference statements)
1
78
0
1
Order By: Relevance
“…The effect of probiotics on glucose metabolism in various mice models and suitable human epithelial cell lines was assessed by several studies 30,31 all highlighting a decrease in fasting or postprandial glucose and HbA1c after probiotics intake. Probiotic yogurt intake was demonstrated to considerably enhance glucose metabolism in some studies on probiotics, while other studies did not present any improvements 14,32 .…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…The effect of probiotics on glucose metabolism in various mice models and suitable human epithelial cell lines was assessed by several studies 30,31 all highlighting a decrease in fasting or postprandial glucose and HbA1c after probiotics intake. Probiotic yogurt intake was demonstrated to considerably enhance glucose metabolism in some studies on probiotics, while other studies did not present any improvements 14,32 .…”
Section: Discussionmentioning
confidence: 98%
“…Previous published data have demonstrated the essential role of gut microbiota in influencing the functioning of gut metabolism like lipids, proteins and carbohydrates decomposition, energy and nutrients absorption and gut motility 10,11 . Recent research associates MS with particular disorders in gut microbiota [12][13][14] . It was also suggested that probiotic intake has a positive impact on some clinical elements of MS 14 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 5 domains: reporting, external validity, internal validity (bias), internal validity (confounding), and power, 27 items were included in the checklist. After evaluation, the studies were classified into: excellent (between 26-28), good (between (20)(21)(22)(23)(24)(25), fair (15)(16)(17)(18)(19) and poor (less than 14) according to their scores.…”
Section: Quality Appraisalmentioning
confidence: 99%
“…In the context of obesity, type 2 diabetes and inflammation, eCB is an essential regulatory system reported to include glucose and energy metabolism [22]. Human and animal trials showed a positive correlation between A. muciniphila intervention and obesity and metabolic disorders [23]. Moreover, it has been demonstrated that A. muciniphila can be involved in anti-cancer immune therapy [24] and may prevent from atherosclerosis [25].…”
Section: Introductionmentioning
confidence: 99%